Strategic Role Of Women In Preserving Culture And Enhancing Family Economy - Andi Annisa Sulolipu; Andi Tenri Ampa (International Journal of Education, Vocational and Social Science, 2025)
This study aims to examine the extent to which women can preserve the cultural heritage of weaving and enhance family economy. This research employs a qualitative approach with a phenomenological perspective. Data collection is done through observation, in-depth interviews, and documentation. Data analysis follows a four-step process: data collection, data reduction, data presentation, and conclusion drawing. The validity test of the data includes: (1) data credibility, (2) transferability (external validation/generalization), (3) dependability (reliability), and (4) confirmability (objectivity). The results of the study indicate that women play a crucial role in preserving the weaving cultural heritage of Donggala Regency, Central Sulawesi, which is one of the educational tourism destinations and specialty souvenirs, and significantly contributes to enhancing the family economy as weavers, which is their primary occupation.